Combining Cancer Immunotherapy and Targeted Therapy - Ribas, Antoni (2013)
The ability to pharmacologically modulate key signaling pathways that drive tumor growth and progression, but do not negatively impact the function of lymphocytes, provides avenues for rational combinatorial approaches to improve the antitumor activity of tumor immunotherapies. Novel targeted agents can very specifically block oncogenic events in cancer cells, leading to a pro-apoptotic milieu and a potential increase in sensitivity to recognition and attack by cytotoxic T lymphocytes. Furthermore, targeted pathway modulation in lymphocytes may change their function and have activating effects in some instances. When tested together with recently developed powerful tumor immunotherapies, such combinations may exploit the highly specific targeting of oncogenes with small molecule inhibitors to lead to high frequency of tumor regressions, and merge this benefit with the durable responses achievable with effective tumor immunotherapies.